The Effect of Profitability, Company Value, and Environmental Social and Governance (Esg) on Tax Avoidance (Empirical Study on Infrastructure Companies on the Indonesia Stock Exchange in 2016-2022) - Dalimah; Rosita Wulandari (Formosa Journal of Applied Sciences, 2024)
The objective of this study is to examine the impact of profitability, firm value, and ESG factors on Tax Avoidance. The present study undertakes an analysis of the financial reports of infrastructure sector firms that are publicly listed on the Indonesia Stock Exchange (BEI) over the timeframe spanning from 2016 to 2022. The study utilized a sample of 61 infrastructure sector firms that were listed on the Indonesia Stock Exchange between 2016 and 2022. The selection of these companies was done using purposive sampling methods. The data employed in this study consists of secondary data, namely financial records obtained from each firm included in the research sample. The initial independent variable in this study is profitability (X1), followed by firm value (X2) as the second independent variable. The third independent variable is Environmental Social and Governance (ESG), and the dependent variable is Tax Avoidance (Y). The research methodology employed in this work was the panel data regression approach. Application of Eviews 12 Student Version Lite software for the analysis of study findings. The research findings indicate that the Random Effect Model (REM) is the most optimal model. The findings of this study indicate that Tax Avoidance is influenced by profitability, firm value, and Environmental Social and Governance (ESG) factors concurrently